A Study on Positions and Functions of Wh-Question Words in Amanatun Dialect of Meto Language - Anselmus Sahan; Imanuel Kamlasi (Universitas Lancang Kuning, 2017)
This study is a descriptive study which mainly deals with the positions of WH-question words in Amanatun dialect of Meto language. The purposes of this research are to identify the positions of WH-questions words in sentence constructions and propose the best way for teaching English to the Meto background students. Analyzing the data, it used translation instrument by asking them to translate sentences of Indonesia into Amanatun dialect. The findings analyzed by using syntactical analysis show that sa (what) takes the initial and the final that function to ask object (choice), reason subject (condition), and gets one variation, that is, sa to sa’a because of its initial position. sekau taking the middle position, functions to ask for object and possession, and the final position functions to ask for object. esme (where) getting ten (10) variations depending on the subject of the sentences takes the final position to ask for place (location). However, esme gets changes on its form because of the subject of the sentences, dialect and tradition of Meto speakers. Its variations are etme/esme, alme/neome, and nbime, elme/esme, onme/meome, meome, and mbime, alme/onme, neome and etme/esme/alme. leka (when) just gets one variation, that is, lek‟at. It happens because the subject is between lek’at and verb mnao (go) while lek‟at takes the front position. Nansa (why) gets some variations, such as nansa, neosa, nak’onme, and ’moe’na’ onme. It takes the initial and final position and functions to ask questions about reason. Onme (how) functions to ask about manner, condition and opinion. Fauk (How many/how much) asks questions about many, much and old.